Potential Legal Protection for Oil Products Sumbawa NTB in the Context of Geographical Indications - Efrilya Rhaswika; Hasbir Paserangi; Marwah Marwah (Jurnal Hukum Volkgeist, 2022)
Since the foundation of the Asean Economic Community (AEC), rapid economic competitiveness has made it easier to get company licenses and enhanced worldwide competition. The Indonesian people must increase their inventiveness and preserve the intellectual property rights (IPR) of the goods they produce, lest they be appropriated by other nations. In spite of the fact that the adoption of Geographical Indications (GI) can greatly boost sales value and the number of products marketed, Indonesia still lacks legal rules for GI that could safeguard Indonesian exports worldwide. Sumbawa Oil is one of the finest products that has the potential to become GI. This research is an empirical legal study that evaluates facts congruent with field observations. Researchers will investigate the characteristics of Sumbawa oil products for their potential to be protected by GI, as well as the role of the West Sumbawa Regional Government in promoting the registration as GI in order to improve the economic health of the business community. Consequently, Sumbawa oil consists of two variables: natural factors and human ones. The government has also aided the community in laboratory testing by BPOM so that the test findings meet the requirements for sale and registration as Sumbawa Oil with Geographical Indication.